Entrepreneurship Education and Founding Passion: The Moderating Role of Entrepreneurial Family Background - Lee, Younggeun; Cortes, Andres Felipe; Joo, Minjoo (Frontiers in Psychology, 2021)
In this paper, we examine the relationship between entrepreneurship education and entrepreneurial passion. Despite the advancement of entrepreneurship education literature and the increasing focus on entrepreneurship education in business schools, we lack empirical exploration on how entrepreneurship education can impact students’ passion for founding new organizations. We hypothesize that students who take entrepreneurship classes would develop high levels of founding passion due to a great perception of skills and abilities that increase positive emotions and decrease negative emotions about the entrepreneurship process. Moreover, we draw on the literature on role models to suggest that students’ entrepreneurial family background (students whose immediate family members are entrepreneurs) strengthens the influence of entrepreneurship education on entrepreneurial passion. Utilizing survey data collected from 160 university students, we found that entrepreneurship education positively influences students’ founding passion and that this relationship is strengthened when students have entrepreneurs in their immediate family.